Between the Feminine and the Masculine – the Image of the Family and Relationships in Melchior Wańkowicz's "Szczenięce lata" - Piechota, Magdalena (Porównania, 2025)
The article considers the role how childhood and youth are mythified in the narrative memoirs of Melchior Wańkowicz, entitled "Szczenięce lata". The future writer and reporter was shaped in two opposing worlds – feminine and masculine. This separation is reflected in the construction of the story. These two spaces are archetypally charged and represent different systems of values, connected with feminine and masculine needs and visions of life. Reminiscing as an adult, the author idealizes the image of these two realities.